Community perception towards employment of people with Down syndrome in Malaysia : a mixed-method study. - Md Mizanur, Rahman; Hock, Ting Chuong; Razitasham, Safii; Rosalia, Saimon; Chen, Yoke Yong; Sharifa Ezat, Wan Puteh; Abg Safuan, Adenan (Francis and Taylor, 2025)
This study examines the employability of people with Down syndrome (PDS) by assessing knowledge, attitudes, productivity and challenges from a community perspective. A concurrent parallel mixed methods design combined quantitative data from 104 surveys and qualitative data from 32 unstructured interviews, providing a multifaceted understanding of the issue. Quantitative data were analysed using descriptive statistics and Spearman rank correlation, while qualitative data were examined with Braun and Clarke’s thematic analysis. Results showed moderate knowledge of PDS employability rights and legal information but significant gaps in procedural knowledge. Attitudes were generally positive, supporting inclusive employment policies. Productivity perceptions were moderately positive, with societal ignorance and cost concerns noted as challenges. Qualitative findings supported these results and emphasised the need for better PDS training, support and the identification of communication barriers and physical and cognitive limitations. This study highlights the need to improve community knowledge, foster positive attitudes and address challenges to enhance PDS employability. Recommendations include targeted education programmes, supportive work environments, robust policy enforcement and specialised training programmes for PDS and potential employers to bridge communication barriers and address physical and cognitive limitations.